Joshua A. Fishman: The Impact of Nationalism on Language Planning ; N. N. Cheboksarov: The Process of National Consolidation in the Countries of Southern and South Easter Asia - Uribe-Villegas, Oscar (Revista Mexicana de Sociología, 2024)
-